2013
DOI: 10.1530/joe-13-0125
|View full text |Cite
|
Sign up to set email alerts
|

Serum anti-Müllerian hormone (AMH) levels correlate with infrarenal aortic diameter in healthy older men: is AMH a cardiovascular hormone?

Abstract: Anti-Mü llerian hormone (AMH) is a gonadal hormone present in the blood in men and pre-menopausal women. AMH regulates male sexual differentiation but has no putative function in adulthood. In recent studies, high AMH levels are associated with absence of cardiovascular disease in men and smaller atherosclerotic burden in monkeys. Mechanistically, AMH has downstream convergence with known regulators of the cardiovascular system, while the specific receptor for AMH is present in murine aorta and the human heart… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
36
2
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(39 citation statements)
references
References 31 publications
0
36
2
1
Order By: Relevance
“…Dennis et al introduced AMH as a novel regulator of the cardiovascular system and declared that serum AMH levels in healthy older men inversely correlate with the diameter of their abdominal aorta [9]. In this regard, related animal studies on AMH association with atherosclerosis are available for rhesus monkeys [44].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Dennis et al introduced AMH as a novel regulator of the cardiovascular system and declared that serum AMH levels in healthy older men inversely correlate with the diameter of their abdominal aorta [9]. In this regard, related animal studies on AMH association with atherosclerosis are available for rhesus monkeys [44].…”
Section: Discussionmentioning
confidence: 99%
“…An applicable implication of our observations is that AMH nomograms in men might provide information regarding different health statuses. Although, data is limited in this regard, recent evidence states that AMH is no longer a mere reproductive hormone and perhaps has regulatory effects in diseases like lung cancer[46] or as above mentioned in cardiovascular disorders [9]. …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In particular, recent experimental and observational studies have identified AMH as a potential influencing factor of cardiovascular function or risk factors of CVD. [14][15][16][17][18] To date, no studies have investigated a direct link between AMH and clinical CVD occurrence. Therefore, in this study, we aimed to determine whether an independent relationship exists between longitudinal trajectories of AMH and clinically manifest CVD in women from the general population.…”
mentioning
confidence: 99%
“…Men with enlarged aortic diameter are also reported to have lower AMH levels [8]. In contrast men, free of arterial cardiovascular disease had higher AMH levels which were similar to levels of AMH in younger men [4].…”
Section: Introductionmentioning
confidence: 80%